Terroir Tourism: Experiences in Organic Vineyards - Byron Marlowe (Beverages, 2019)
This article considers key determinants of terroir tourism in the context of organic vineyards in Oregon, US. Emerging from anthropology, climatology, ecology, geography and wine tourism, terroir tourism has been recently recognized to have potential for developing tourism in Oregon. However, research has sought to determine terroir tourism and its characteristics, differentiating it from wine tourism. This case of Oregon will investigate a wine territory through the examination of organic vineyards. The relative importance of terroir within the organic vineyard destinations of Oregon is examined. Determining the characteristics of terroir tourism from a review on terroir and the experience economy 4E framework on wine tourism develops the case into organic vineyards with terroir tourism characteristics. Ultimately, an attempt to further develop wine tourism destinations based on their unique terroir esthetic experiences, and the potential for terroir tourism within the experience economy, is developed.